Japanese scoring systems to predict resistance to intravenous immunoglobulin in Kawasaki disease were unreliable for Caucasian Israeli children. (25th June 2018) - Arane, Karen; Mendelsohn, Kerry; Mimouni, Michael; Mimouni, Francis; Koren, Yael; Brik Simon, Dafna; Bahat, Hilla; Hanna Helou, Mona; Mendelson, Amir; Hezkelo, Nofar; Glatstein, Miguel; Berkun, Yackov; et al.
Abstract: Aim: This study assessed the validity of using established Japanese risk scoring methods to predict intravenous immunoglobulin (IVIG) resistance to Kawasaki disease in Israeli children. Methods: We reviewed the medical records of 282 patients (70% male) with Kawasaki disease from six Israeli medical centres between 2004 and 2013. Their mean age was 2.5 years. The risk scores were calculated using the Kobayashi, Sano and Egami scoring methods and analysed to determine whether a higher risk score predicted IVIG resistance in this population. Factors that predicted a lack of response to the initial IVIG dose were identified. Results: We found that 18% did not respond to the first IVIG dose. The three scoring methods were unable to reliably predict IVIG resistance, with sensitivities of 23%–32% and specificities of 67%–87%. Calculating a predictive score that was specific for this population was also unsuccessful. The factors that predicted a lacked of response to the first IVIG dose included low albumin, elevated total bilirubin and ethnicity. Conclusion: The established risk scoring methods created for Japanese populations with Kawasaki disease were not suitable for predicting IVIG resistance in Caucasian Israeli children, and we were unable to create a specific scoring method that was able to do this.